(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Mesio-occluso-distal (MOD) cavity preparations significantly weaken posterior teeth by reducing cuspal stiffness and increasing susceptibility to fracture. Fibre-reinforced composite systems have been introduced to enhance the mechanical performance and longevity of restorations. Aim & Objective: To compare the fracture resistance and failure patterns of MOD cavities restored with short fibre composite, long fibre reinforcement, and Ribbond reinforcement with those restored using conventional composite resin. Materials & Methods: Forty extracted human molars with standardized MOD cavity preparations were randomly allocated into four groups (n = 10 each): Group I (conventional composite), Group II (short fibre composite), Group III (long fibre reinforcement), and Group IV (Ribbond reinforcement). Following restoration, specimens underwent compressive loading in a universal testing machine until fracture. Fracture resistance was recorded in Newtons (N), and failure modes were classified as restorable or non-restorable. Data were analyzed using one-way ANOVA and Tukey’s post-hoc test. Results: Fracture resistance differed significantly among the groups (F = 1357.26, p < 0.001). Group II showed the highest mean fracture resistance (1197.50 ± 15.14 N), followed by Group III (1037.50 ± 15.14 N), Group IV (956.30 ± 9.83 N), and Group I (787.00 ± 16.02 N). Compared with the control group, short fibre, long fibre, and Ribbond reinforcement increased fracture resistance by 52.2%, 31.8%, and 21.5%, respectively. Reinforced restorations also demonstrated a higher proportion of restorable fractures, with the short fibre group showing the most favorable failure pattern (80%). Conclusion: Fibre reinforcement significantly improves fracture resistance and promotes more favorable failure modes in MOD restorations. Short fibre composite demonstrated the best overall performance.